The Signaling Paradox: Revisiting the Impacts of Overeducation in the Chinese Labor Market - Bingbing Zhang; Qinggen Zhang; Congli Yao; Zhiyuan Liu (MDPI AG, 2024)
With the widespread popularization of higher education, the increased supply of knowledge laborers has heightened the risk of overeducation, posing a significant threat to employment quality. Utilizing data from the CGSS2015 survey, this study controls for selection bias by matching employed and self-employed individuals using Propensity Score Matching (PSM) to distinguish and estimate the signaling and productivity effects of overeducation in China. The findings indicate that the signaling effects of overeducation are not significant, challenging the Weak Screening Hypothesis (WSH) and suggesting that overeducation in China is not genuine overeducation. It is also acknowledged that overeducation has dual productivity effects, including the loss of personal productivity and the promotion of job productivity. This implies that overeducation has contributed to the increase of social productivity at the cost of personal sacrifice.